Crucial conversations - Grenny, Joseph; Patterson, Kerry, 1946-; McMillan, Ron; Switzler, Al; Gregory, Emily, 1975- (McGraw Hill, 2022)
"Keep your cool and get the results you want when faced with crucial conversations. This New York Times bestseller and business classic has been fully updated for a world where skilled communication is more important than ever. The book that revolutionized business communications has been updated for today's workplace. Crucial Conversations provides powerful skills to ensure every conversation-especially difficult ones-leads to the results you want. Written in an engaging and witty style, the book teaches readers how to be persuasive rather than abrasive, how to get back to productive dialogue when others blow up or clam up, and it offers powerful skills for mastering high-stakes conversations, regardless of the topic or person. This new edition addresses issues that have arisen in recent years. You'll learn how to: Respond when someone initiates a crucial conversation with you Identify and address the lag time between identifying a problem and discussing it Communicate more effectively across digital mediums When stakes are high, opinions vary, and emotions run strong, you have three choices: Avoid a crucial conversation and suffer the consequences; handle the conversation poorly and suffer the consequences; or apply the lessons and strategies of Crucial Conversations and improve relationships and results. Whether they take place at work or at home, with your coworkers or your spouse, crucial conversations have a profound impact on your career, your happiness, and your future. With the skills you learn in this book, you'll never have to worry about the outcome of a crucial conversation again"--